Perlindungan Konsumen terhadap Hilangnya Saldo Uang Elektronik Berbasis Server (Studi Kasus Aplikasi DANA di Kota Jambi) - Nur Matasari, Lala (Zaaken: Journal of Civil and Business Law, 2025)
The purpose of the study is to understand and analyze the form of consumer protection against the loss of server-based electronic money. The research method used in this thesis is Empirical Jurisprudence using the interview method. The results of the study indicate that there is a lack of adequate legal protection for E-wallet users in dealing with the problem of losing balances that occur in the digital payment system. Where E-wallet users often experience problems with their balances decreasing for no apparent reason, where complaints of obstacles experienced by consumers are not resolved properly both materially and immaterially. This can occur due to system errors, personal data leaks, fraud or unauthorized access from third parties. This problem also arises due to the lack of strict legal protection. legal protection provided to E-wallet users in Indonesia is still considered weak and inadequate. Unclearness about the rights and obligations of service providers and consumer protection in digital transactions, including misuse or loss of balance. the need for improvements in strengthening the security system, transparency of communication, and efficiency in the balance return process to increase protection for E-wallet users in facing the risk of losing their balance. This causes losses to consumers who have spent their time and money, but consumers have never made demands for their rights to the Payment System Service Provider or referred to as business actors.